The Impact of a Large Parental Leave Benefit Reform on the Timing of Birth around the Day of Implementation - Marcus Tamm (Oxford Bulletin of Economics and Statistics, 2013)
The introduction of the German parental leave benefit (Elterngeld) applied to all children born on 1 January, 2007 or later. The Elterngeld considerably changed the amount of transfers to families during the first two years postpartum. We show that the incentives created by using a cut-off date led more than 1,000 parents to postpone the delivery of their children from December 2006 to January 2007. Concerning potential adverse impacts on health outcomes of children we find a slight increase in average birth weight and the rate of children with high birth weight (>4,000 g).
Keywords: H31; J13; 330